If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(x+3)=7x+12-3x
We move all terms to the left:
4(x+3)-(7x+12-3x)=0
We add all the numbers together, and all the variables
4(x+3)-(4x+12)=0
We multiply parentheses
4x-(4x+12)+12=0
We get rid of parentheses
4x-4x-12+12=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| 6x-6=32 | | 4x=(4x+3)2 | | 7v+23=4+8v-22 | | 2x2-9+4=0 | | -13k=-26 | | 0.08(y-5)+0.20y=0.18y-0.6 | | -4-8d=-12 | | X/2+10=4x/3 | | (3x+3)+45=x | | x2-4x+9=0 | | (3x+3)45=x | | 7=1n-2+2 | | 36/k-7=5 | | (3/2)x=-8 | | 2.3+10m=6.18 | | 6(2a+4)^2=(2a+4)+2 | | 2x-12=6(3-x) | | 2x2-12x-18=0 | | $50+0.99n=1.89n | | 8x-(3x-7)=42 | | 27+9=52x+40x | | -.25a-4=1.75-3 | | 4+x=16+x2 | | 12a+24-2=0 | | 3.8+10m=7.53 | | 0.50x+0.35(50)=28.5 | | 6x2=9x-3 | | 500=16x | | (3-5)^2-8d=-12 | | 9y+10y=-2.6 | | 1/5x2-3/5x-18/5=0 | | 5x+6=5+3x+19 |